2014
DOI: 10.1002/bem.21864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 60‐GHz millimeter waves and corresponding heat effect on endoplasmic reticulum stress sensor gene expression

Abstract: Emerging high data rate wireless communication systems, currently under development, will operate at millimeter waves (MMW) and specifically in the 60 GHz band for broadband short-range communications. The aim of this study was to investigate potential effects of MMW radiation on the cellular endoplasmic reticulum (ER) stress. Human skin cell lines were exposed at 60.4 GHz, with incident power densities (IPD) ranging between 1 and 20 mW/cm(2) . The upper IPD limits correspond to the ICNIRP local exposure limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…We reported that levels of several stressinducible genes were not significantly enhanced [29,32], suggesting that MMW around 60…”
Section: Discussionmentioning
confidence: 87%
“…We reported that levels of several stressinducible genes were not significantly enhanced [29,32], suggesting that MMW around 60…”
Section: Discussionmentioning
confidence: 87%
“…Nicolaz et al [22] described that exposure to 60.4 GHz radiation at a power density of 0.14 mW/cm 2 did not cause endoplasmic reticulum stress in human glial cells. Le Dréan’s group has also published studies on the effects of 60.4 GHz radiation [23,24,25]. Le Quément et al [23,24] showed no significant differences in gene expression following exposure to millimeter-wavelength radiation: although after 6 h exposure at 20 mW/cm 2 real-time PCR analysis showed that some gene expression levels were affected, and this effect was linked to the increased temperature caused by exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Le Dréan’s group has also published studies on the effects of 60.4 GHz radiation [23,24,25]. Le Quément et al [23,24] showed no significant differences in gene expression following exposure to millimeter-wavelength radiation: although after 6 h exposure at 20 mW/cm 2 real-time PCR analysis showed that some gene expression levels were affected, and this effect was linked to the increased temperature caused by exposure. Haas et al [25] also indicated that a slight increase in protein expression observed following exposure to 60.4 GHz for 24 h was related to heating, and that there were no differences in the protein expression of neuronal marker β-tubulin or in the internal expression of control β-tubulin, consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…Before exposure, the medium was replaced by DMEM without sodium bicarbonate (Ref. 12800‐017; Thermo Fisher Scientific, Waltham, MA) containing 4.6 mM of Hepes (Thermo Fisher Scientific) to maintain constant pH in the non‐gassed incubator of the exposure system [Le Quément et al, ]. SUT 4 . Agar gel (98.5% of distilled water and 1.5% of agar) was used as a reference water‐equivalent model without convection.…”
Section: Methodsmentioning
confidence: 99%